Ekospiritual: Relasi Alam dan Manusia dalam Pandangan berbagai Agama - Encep Encep; Hamdani Anwar; Nur Afiyah Febriani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This paper discusses two basic issues regarding the problem of the ecological crisis in relation to religion. First, because of the belief that the root of the catastrophe of environmental damage is caused by the dwindling spirituality of modern humans. This thinness of spirituality causes them to lose touch with the sacredness of all things. Until in the end they assumed that nature was only limited to objects that could be exploited freely. Meanwhile, spiritual issues are a core part of every religion. Second, there are accusations that religion has become the inspiration behind the environmental crisis. Religion, with all its doctrines, is considered to have inspired followers of related religions to exploit nature. The method used is qualitative and in the discussion it uses descriptive analysis to reveal and explain ecospiritual in the Qur'an. This paper concludes that in fact religions view the ecospiritual, especially regarding the creation of nature, the sacredness of nature and the relationship between humans and nature, in short it can be concluded that Islam, Christianity, Confucianism, and Judaism have the same perspective on the creation of nature. These religions explain that nature was created by God, but unlike Hinduism and Buddhism, the two religions do not provide an opinion regarding the creation of nature. Then, regarding the sacredness of nature, Islam, Christianity, Hinduism, Buddhism, and Judaism explain that Nature is sacred. However, not with Confucianism, this religion does not have any opinion about the sacredness of nature. Finally, regarding the relationship between humans and nature, the seven religions state that the relationship between humans and nature is the same, the similarities are elements of creation.Keywords: Ecospiritual, Nature and Human Relations, Religion. Abstrak. Tulisan ini membahas dua hal mendasar mengenai permasalahan krisis ekologi kaitannya dengan agama. Pertama, karena adanya keyakinan bahwa akar dari malapetaka kerusakan lingkungan itu disebabkan oleh spiritualitas manusia modern yang semakin menipis. Tipisnya spiritualitas ini menyebabkan mereka kehilangan kontak dengan sakralitas segala sesuatu. Hingga pada akhirnya beranggapan bahwa alam hanyalah sebatas benda yang bisa dieksploitasi secara bebas. Sementara itu, persoalan spiritual adalah bagian inti dari setiap agama. Kedua, karena adanya tudingan yang menyebut bahwa agama telah menjadi inspirator dibalik krisis lingkungan. Agama, dengan segala doktrinnya, dianggap telah menginspirasi para pengikut agama terkait untuk melakukan eksploitasi terhadap alam. Metode yang digunakan adalah kualitatif dan dalam pembahasannya menggunakan deskriftif analisis untuk menyingkap serta menjelaskan ekospiritual di dalam Alquran. Tulisan ini memberikan kesimpulan bahwa sesungguhnya agama-agama memandang tentang ekospiritual khususnya terkait penciptaan alam, sakralitas alam dan relasi antara manusia dengan alam, secara singkat dapat disimpulkan bahwa Agama Islam, Kristen, Kong Hu Cu, dan Yahudi memiliki kesamaan perspektif mengenai penciptaan alam. Agama-agama tersebut menjelaskan bahwa alam diciptakan oleh Tuhan, namun berbeda dengan agama Hindu dan Budha, kedua agama tersebut tidak memberikan pendapat terkait penciptaan alam. Kemudian, mengenai sakralitas alam, agama Islam, Kristen, Hindu, Budha, dan Yahudi menjelaskan bahwa Alam itu suci. Namun, tidak dengan agama Kong Hu Cu, agama tersebut tidak berpendapat apapun tentang sakralitas alam. Terakhir, mengenai relasi manusia dan alam ketujuh agama tersebut menyebutkan bahwasannya hubungan manusia dan alam adalah sama, persamaannya tersebut merupakan unsur penciptaan.Kata Kunci: Ekospiritual, Relasi Alam dan Manusia, Agama